Altered expression of long noncoding RNAs regulating neutrophilic inflammation in peripheral blood was associated with symptom severity in patients with house dust mite-induced allergic rhinitis - Zhao, Jinming; Pu, Xiaoyu; Wang, Xiangdong; Zhang, Luo (Frontiers in Allergy, 2024)
BackgroundLong noncoding RNAs (lncRNAs) have been implicated in a diverse array of human immune diseases; however, a comprehensive understanding of the expression and function of lncRNAs in the peripheral blood leukocytes of individuals suffering from house dust mite (HDM)-induced allergic rhinitis (AR) remains elusive.ObjectiveTo explore the potential roles and functions of long noncoding RNAs (lncRNAs) in the pathogenesis of AR.MethodsSequencing analysis was performed on peripheral blood leukocytes collected from patients with HDM-induced AR and healthy controls (HCs) to elucidate the expression patterns of lncRNAs. Differentially expressed (DE) lncRNAs were identified and validated, and further correlation analyses were conducted to explore their associations with visual analog scale (VAS) scores and cytokine levels in the serum and nasal secretions. Additionally, bioinformatics analyses were performed to predict the potential pathways influenced by DE lncRNAs. Finally, the diagnostic potential of these lncRNAs in AR was assessed via receiver operating characteristic (ROC) curve analysis.ResultsSignificant differences in the expression profiles of lncRNAs and mRNAs were detected between AR patients and HCs. Four lncRNAs were markedly upregulated in AR patients. AC011524.2 was positively correlated with nasal pruritus (r = 0.4492, P = 0.0411). AL133371.3 was positively correlated with runny nose (r = 0.4889, P = 0.0245). AC011524.2 was positively correlated with CXCL8 (r = 0.4504, P = 0.0035). AL133371.3 was significantly positively correlated with only IL-17 (r = 0.4028, P = 0.0100). IL-4 in the serum was positively related to IL-17 in the serum (r = 0.4163, P = 0.0002). CXCL5 in the serum was positively correlated with IFN-γ (r = 0.3336, P = 0.0354) in nasal secretions. The area under the curve (AUC) of the ROC curve resulting from the integration of the 4 lncRNAs exhibited a remarkable value of 0.940 for AR diagnosis.ConclusionsOur results identified several lncRNAs associated with AR symptoms and inflammatory cytokines. Specifically, AC011524.2 and AL133371.3 exhibited strong correlations with diverse AR manifestations and serum cytokines, suggesting their pivotal role in the pathogenesis of AR, likely via neutrophil- and Th17-related pathways. However, the precise underlying mechanisms are still elusive, necessitating further exploration.